The Influence of Structured Physical Activity and Family Support on Mother's Readiness to Face Childbirth in the Independent Practice of Midwife Mila Ba'diawati Serang Banten - Resi Galaupa; Mila Ba’diawati (International Journal Of Health Science, 2023)
The data shows a downward trend in the MMR indicator (per 100,000 live births) from 390 in 1991 to 230 in 2020 or a decrease of -1.80 percent per year. Despite the decline, MMR still has not reached the 2015 MDGs target, which is 102 and the 2030 SDGs, which is less than 70 per 100,000 live births. On the IMR indicator, data shows a downward trend from 68 in 1991 to 24 in 2017 or a decrease of -3.93 percent per year. Similar to MMR, the reduction rate for IMR has not reached the 2015 MDGs target of 23 and the 2030 SDGs target of 12. The purpose of this study was to determine the Effect of Structured Physical Activity and Family Support on Mother's Readiness to Face Childbirth at the Independent Practice of Midwife Mila Ba'diawati Serang Banten Year 2022. This research method uses an analytical survey with a cross sectional design. The sample in this study were third trimester pregnant women as many as 32 respondents, the sampling technique was total sampling. Data analysis using chi square. The results of the study showed that there was a significant relationship between structured physical activity (0.011 <0.05), family support (P-Value < 0.022) with readiness for childbirth at Midwife Mila Ba'diawati Serang Banten Independent Practice in 2022.So that this research is expected to be able to provide education and informationabout readiness for labour.